2017
DOI: 10.1111/dme.13364
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of silent myocardial ischaemia prevalence and cardiovascular disease risk factor management in Type 2 diabetes over a 10‐year period: an observational study

Abstract: The prevalence of silent myocardial ischaemia decreased sharply over time, and control of the main cardiovascular disease risk factors improved. Although the causality link cannot be established, the present study supports current recommendations advocating glycaemic control and intensive management of cardiovascular factors instead of systematic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Furthermore, the number of additional cardiovascular risk factors and the presence of diabetic complications, especially nephropathy and cardiac autonomic neuropathy play a role [3,4]. The prevalence of silent ischemia which was 20-30% in the 1990's [4] has dropped in the last decade [5]. Some recent studies showed that coronary computed tomography angiography (CCTA) may detect coronary artery stenoses in a large proportion of asymptomatic patients with diabetes [6,7].…”
mentioning
confidence: 99%
“…Furthermore, the number of additional cardiovascular risk factors and the presence of diabetic complications, especially nephropathy and cardiac autonomic neuropathy play a role [3,4]. The prevalence of silent ischemia which was 20-30% in the 1990's [4] has dropped in the last decade [5]. Some recent studies showed that coronary computed tomography angiography (CCTA) may detect coronary artery stenoses in a large proportion of asymptomatic patients with diabetes [6,7].…”
mentioning
confidence: 99%
“…Peripheral vascular disease has been shown to be independently associated with silent CAD in several studies [11,39,45,108,110,111]. Rajagopalan et al [39] concluded that ECG Q waves, and peripheral artery disease (OR 2.134, CI 1.150-3.961; P = 0.016) were the 2 most important variables associated with high risk findings on stress SPECT, in their analysis.…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 99%
“…It is also clinically relevant to underline that myocardial ischemia can resolve, as demonstrated in the DIAD study, after patients underwent intensive CV risk factor control; in follow-up of the DIAD study, resolution of ischemia was found in 79% of 71 T2DM patients who initially had abnormal studies, after 3 years of optimal medical treatment [44]. Moreover, the prevalence of silent CAD seems to reduce over time: a French cohort of 770 T2DM, prospectively followed-up for a 10-year period, showed a progressive and steady reduction of SMI from 22.6% in 1999-2002, to 13.7% in 2003-2005 and to 5.9% in 2006-2009 (P < 0.0001) [45].…”
Section: The Clinical Relevance Of Silent Coronary Artery Disease In mentioning
confidence: 99%
“…Furthermore, the number of additional cardiovascular risk factors and the presence of diabetic complications, especially nephropathy and cardiac autonomic neuropathy play a role (3,4). The prevalence of silent ischemia which was 20-30% in the 1990's (4) has dropped in the last decade (5).…”
Section: Introductionmentioning
confidence: 99%